Climate change, air pollution and human health. (1st October 2022) - Vandyck, Toon; Ebi, Kristie L; Green, Donna; Cai, Wenjia; Vardoulakis, Sotiris
Abstract: This article takes stock of recent literature on health impacts of climate change and air pollution, and the corresponding health benefits of policy action aiming to reduce greenhouse gas and air pollutant emissions. We focus particularly on the publications in the Focus Collection on 'Climate Change, Air Pollution and Human Health', which illustrate advances in three key research areas. First, the impacts of global warming and air pollution are unevenly distributed, as they disproportionately affect vulnerable socio-economic groups including older adults, pregnant women, children, and people with lower earnings or education levels. Second, recent research improves our understanding and quantification of impacts identified in earlier work, and explores novel impact pathways such as the associations between allergies and climate change, and between air pollution and diabetes mellitus, Alzheimer's disease and Parkinson's disease. Third, significant synergies in tackling climate change and air pollution can strengthen the case for ambitious policy action. These synergies are heterogeneous across sectors and regions, point to low-hanging fruit among policy options (e.g. phasing out coal), and provide a strong basis for broader sustainable development, improving health and gender equality. Finally, we point out suggestions for future research. Research advances can guide policies to mitigate future climate change, air pollution and the associated health impacts, while informing adaptation strategies that aim to protect the health of the most vulnerable in society.